The expansion of genes encoding soluble silk components in the greater wax moth, Galleria mellonella. (March 2019) - Kludkiewicz, Barbara; Kucerova, Lucie; Konikova, Tereza; Strnad, Hynek; Hradilova, Miluse; Zaloudikova, Anna; Sehadova, Hana; Konik, Peter; Sehnal, Frantisek; Zurovec, Michal
Abstract: Lepidopteran silk is a complex assembly of proteins produced by a pair of highly specialized labial glands called silk glands. Silk composition has been examined only in a handful of species. Here we report on the analysis of silk gland-specific transcriptomes from three developmental stages of the greater wax moth, Galleria mellonella, combined with proteomics, Edman microsequencing and northern blot analysis. In addition to the genes known earlier, we identified twenty seven candidate cDNAs predicted to encode secretory proteins, which may represent novel silk components. Eight were verified by proteomic analysis or microsequencing, and several others were confirmed by similarity with known silk genes and their expression patterns. Our results revealed that most candidates encode abundant secreted proteins produced by middle silk glands including ten sericins, two seroins, one or more mucins, and several sequences without apparent similarity to known proteins. We did not detect any novel PSG-specific protein, confirming that there are only three fibroin subunits. Our data not only show that the number of sericin genes in the greater wax moth is higher than in other species thus far examined, but also the total content of soluble proteins in silk is twice as high in G. mellonella than in B. mori or A. yamamai . Our data will serve as a foundation for future identification and evolutionary analysis of silk proteins in the Lepidoptera. Graphical abstract: Image 1 Highlights: Soluble components of G. mellonella silk make up almost half of the total silk protein mass. Seventeen novel highly or moderately expressed genes were characterized in detail. Putative novel gene products include sericins, mucins and seroins. This study improves our understanding of silk structure and evolution.